Biomechanical Analysis of Cuboid Osteotomy Lateral Column Lengthening for StageⅡB Adult- acquired Flatfoot Deformity: A Cadaveric Study. Issue 3 (11th September 2017) - Yang, Yunfeng; Zhou, Haichao; Zhang, Yun
Category: Basic Sciences/Biologics Introduction/Purpose: To investigate the effect of cuboid osteotomy lateral column lengthening (LCL) for the correction of stage? B adult-acquired flatfoot deformity in cadaver. Methods: Six cadaver specimens were compressively loaded to 350 N. Flatfoot models were established and each was evaluated radiographically and pedobarographically in the following conditions: (1) intact foot, (2) flatfoot, (3) cuboid osteotomy LCL (2, 3, 4, and 5 mm). Results: Compared with the flatfoot model, the 2-, 3-, 4-, and 5-mm LCLs showed significant correction of talonavicular coverage on anteroposterior radiographs and talus-first metatarsal angle on both anteroposterior and lateral radiographs. As the graft increased in size incrementally, lateral forefoot pressure increased consistently, and medial pressure decreased significantly except for the 2-mm LCL. Compared with the intact foot, the above angles of the LCLs showed no significant difference except for the 2- mm LCL. In terms of forefoot pressure, medial pressure of the 2-mm LCL and lateral pressure of the 3-, 4- and 5-mm LCLs showed statistical differences, but lateral pressure of the 3-mm LCL was not much more than the intact foot as compared to the 4- and 5-mm LCLs, which was still less than medial pressure. Conclusion: Cuboid osteotomy LCL procedure avoids damage to subtalar joint and has a good effect on correction of stage? B adult-acquired flatfoot deformity with a 3 mm lengthening in cadavers.